Software quality assurance - Laporte, Claude Y.; April, Alain, 1958- (Wiley-IEEE Computer Society, Inc., 2018)
"This book introduces Software Quality Assurance (SQA) and provides an overview of standards used to implement SQA. It defines ways to assess the effectiveness of how one approaches software quality across key industry sectors such as telecommunications, transport, defense, and aerospace"--